PRODUCTION AND QUALITY EVALUATION OF FIBRE-RICH BISCUIT FROM BLENDS OF WHOLE TIGERNUT (CYPERUS ESCULENTUS L.) AND UNRIPE BANANA (MUSA SPP) FLOUR BLENDS - Agwo, O. E.; Onwuzuruike, U. A.; Uluocha, M. D.; Edima-Nyah, A. P.; Onuchukwu, C. T. (FUDMA JOURNAL OF SCIENCES, 2025)
The use of whole wheat flour has been largely utilized for the production of fibre-rich biscuit, a practice that has limited the exploration of indigenous crops for this purpose. The objective of this study was therefore, to utilize local crops for fibre-rich biscuit production, thereby minimizing their postharvest losses, as well as reduce the dependency on wheat flour. Whole tigernut and unripe banana, used for this study, were processed into flour and blended at various ratios. The flours were analysed for functional properties prior to biscuit production. The biscuit samples were analyzed for proximate composition, mineral content, dietary fibre profile, and physical properties using standard methods. Compeletely randomnized designed was used, and the data obtained was subjected to descriptive analysis using one-way ANOVA at a 95% confidence interval. Functional properties varied: bulk density (0.62-0.86 g/ml), water absorption capacity (1.37-1.88 g/ml), oil absorption capacity (1.29-1.53 g/ml), emulsion capacity (16.70-20.85%), foam capacity (15.28-21.51%), swelling index (2.12-2.49%), and gelatinization temperature (59.00-66.00°C). The nutrient content such as ash (1.75% to 4.33%), protein (4.38 to 9.18%), fibre (1.63% to 5.88%) and fat (13.22 to 16.82%) improved significantly. Fibre profile increased in the composite biscuit samples. Insoluble dietary fibre ranged from 1.95 to 11.72% while soluble dietary fibre ranged from 0.57 to 8.65% respectively. Results of mineral content revealed an improved mineral concentration in the composite samples while the physical properties were comparable to those produced from wheat flour. Conclusively, composite biscuit had improved nutrient properties compared to biscuit from wheat flour. Overall, the 90% whole...
Keywords: Dietary fibre; Micronutrient; Physical; Tigernut; Banana